Regeneration of East Manchester : a political analysis - Blakeley, Georgina; Evans, Brendan, 1944- (Manchester University Press, 2013)
East Manchester was the site of one of the most substantial regeneration projects internationally. Urban regeneration was a central plank of New Labour policy and the approach radically altered with the election of the Coalition Government in 2010. East Manchester was one of the most deprived areas of Britain in 1997, referred to as a `basket case' in dire need of regeneration. This book explores the role of Manchester City Council and other public agencies in the regeneration of the area.